Stock Verification: Some Problems of Electronic Publications - Dhiman, A.K. (DESIDOC Journal of Library & Information Technology, 2003)
This paper discusses the problems that may be faced by a library professional instock verificatioh of electronic publications at present or in near future. The mainemphasis is given towards the stock verification of compact disks (CDs), today'smuch used media. http://dx.doi.org/10.14429/dbit.20.6.3528